Status of Primary Labeling of Medicines Manufactured by Nepalese Pharmaceutical Industries - Shrestha, Binaya; Palikhey, Anjan; Kandel, Kamal (Journal of College of Medical Sciences-Nepal, 2024)
Background Proper medication labeling is essential to meet regulatory requirements and guarantee the safety of patients using the medication. This study aimed to observe the status of primary labeling of medicines manufactured and marketed by Nepalese pharmaceutical industries. Methods A prospective study was conducted between June 2022 to October 2022 in Kathmandu Medical College. Total of 372 primary labeling of medicines manufactured by Nepalese pharmaceutical companies were assessed as required by Drug Standard Regulation, 2043 (1986 AD) of Nepal. Results This study assessed the primary labeling of 372 medications produced by 46 pharmaceutical companies in Nepal. Most of the primary labeling had stated manufacturing company's name, address, and country, the production serial number for the drug, and recommended storage methods. But only 22(5.9%) of them specified the sub-category and appropriate drug classification was found on 352(94.6%) primary label. Conclusions The current study revealed that the status of the primary labeling is satisfactory as majority of the label contained the essential criteria required by Drug Standard Regulation, 2043 (1986 AD) of Nepal.